Immunohistochemical Study of the CD44 Expression in Benign, Borderline and Malignant Surface Epithelial Ovarian Tumors and Metastatic Ovarian Tumors - Yurdakan, Gamze; Onak Kandemir, Nilüfer; Çolak, Sacide; Ege Gül, Aylin; Karadayı, Nimet; Özdamar, Şükrü Oğuz (Gynecology Obstetrics & Reproductive Medicine, 2007)
OBJECTIVE: Carcinogenesis and metastasis are multistep processes involving complex interactions between tumor cells and the environment. The main cause of tumor cell movement in invasive carcinomas may be the loss of the intercellular adherence junction. One adhesion receptor, CD44, binds to hyaluronan, an extracellular matrix component. This study investigated a series of benign, borderline, and malignant ovarian serous neoplasms to elucidate the role of CD44. STUDY DESIGN: Paraffin-embedded formalin-fixed blocks from benign serous tumors (n=11), benign mucinous tumors (n= 8), borderline serous tumors (n=6), borderline mucinous tumors (n=1), primary malignant ovarian serous tumors (n=9), and metastatic ovarian tumors (n=12) were stained immunohistochemically for CD44. The percentages of reactive tumor cells and stromal cells with CD44 were scored. The staining intensity was graded from 1+ to 3+. CD44 protein was preferentially expressed along the basolateral domain of the plasma membrane of tumor cells. RESULTS: CD44 was not detected in only 1 (5.2%) benign tumor. The remaining tumors were reactive for CD44 to different degrees and in different locations. CD44 staining was observed in 4 (8.33%), 21 (43.75%), 16 (33.33 %), and 7 (14.58%) of all grade 0, 1, 2, and 3 tumors, respectively. Statistically significant associations were found between serous and mucinous benign tumors (p=0.0001), borderline and malignant serous tumors (p=0.001), malignant serous tumors and metastatic carcinomas (p=0.054), and primary malignant ovarian tumors and metastatic carcinomas (p=0.002) based on the CD44 staining grade. Grade 0,1,2, and 3 stromal staining was seen in 14 (29.16%), 31 (64.58%), 1 (2.08%), and 1 (2.08%) ovarian tumors, respectively, although there was no statistical difference in the CD44 reaction in stromal cells. In primary malignant tumors, CD44 was detected significantly more often than in primary benign ovarian tumors (p=0.0001). CONCLUSION: These results suggest that CD44 expression is important in differentiating between borderline and malignant serous tumors, primary malignant ovarian tumors, and metastatic carcinomas. In addition, CD44 expression is a characteristic factor in the stromal invasion of ovarian serous carcinomas. Additional studies are necessary to verify the prognostic significance of CD44 expression in tumor progression.